Implementation of CC-CV Battery Charging Method with Temperature Control for Level Crossings - Yuli Prasetyo; Santi Triwijaya; Andri Pradipta; Akhwan; Aggie Brenda Vernandez; Akhsay Chandra Dewanta (Journal of Railway Transportation and Technology, 2026)
Level crossings are critical for ensuring the safety of long-distance railway operations. To maintain the reliability of these at-grade crossings, their power supply systems are equipped with lead-acid batteries. This study focuses on the battery charging system. A known effect of battery charging is temperature rise due to charge current flow. The Constant Current-Constant Voltage (CC-CV) method is proposed in this research to address the issue of prolonged charging time while monitoring temperature to preserve battery health. Battery charging tests were conducted by comparing the CC-CV and Switch Mode Power Supply (SMPS) methods, starting from the minimum battery voltage (11.7 V) until the voltage set point was reached. The results show that the SMPS method required 5 hours with an average charging temperature of 34.0°C. In contrast, the CC-CV method required only 2.1 hours with an average temperature of 35.4°C. Therefore, the CC-CV method can significantly accelerate the charging time while ensuring the temperature remains within the specified maximum limit. This shorter charging duration is expected to enhance the reliability and prevent service disruptions at level crossings.